Identification and quantification of benchmarks of milk production systems in Minas Gerais - Matozalém Camilo Neto; José Maurício de Souza Campos; André Soares de Oliveira; Sebastião Teixeira Gomes (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to identify and quantify benchmarks of milk production systems. The technological profile and size, livestock and economic indicators of sixteen farms in the region of Triângulo Mineiro were analyzed. Indicators correlated with rate of return on capital (RRC) were identified and quantified in four scenarios of RRC (6, 8, 10 and 12% per year). The correlated indicators and their respective values in the four scenarios were: land (99, 90, 81 and 73 ha); relation of total cows in lactation (74, 77, 79 and 82%); lactating cows per area (0.89; 0.99; 1.11 and 1.22 cows/ha); milk production per lactating cow (12.04; 13.00; 13.96 and 14.92 liters/cow/day); milk production per total cows (9.19; 10.23; 11.27 and 12.31 liters/cow/day); labor productivity (322, 349, 375 and 402 liters/day/man); land productivity (4351, 5236, 6120 and 7004 liters/ha/year); participation of total effective operational cost of activity in the gross revenue of the activity (69, 66, 63 and 60%); participation of total operational cost of activity in the gross revenue of the activity (80, 76, 72 and 69%); participation of total cost of activity in the gross revenue of the activity (93, 88, 82 and 77%); labor cost in relation to milk gross revenue (15, 13, 11 and 9%); profitability (15, 19, 23 and 28%); and capital investment in the activity in relation to daily milk production (922, 829, 736 and 644 R$/liter-day). The productivity of the factors land and animals present more correlation with profitability than labor productivity, regardless of the production size.